Identification of the Distribution of Leachate in the TPA Terjun, Medan Marelan District, Medan City using the Resistivity 2D Method - Said Muzambiq; Amir Husin; Meutia Nurfahasdi; Roy Monald Dongoran (Jurnal Ilmu Lingkungan)
The 2D resistivity method can provide a more detailed subsurface picture, including the distribution of resistivity values in both vertical and horizontal sections. The results of the geoelectric test show that the leachate distribution in Track I (First) is at a track length of 28 meters – 84 meters, a depth of 13 meteras – 17.4 meters with a resistivity value of 2.18 m, Track II (Scond) is at a track length of 7 meters. – 140 meters, 8.93 meters deep – 13.4 meters with a resistivity value of 2.95 m, and Track III (Third) along 80 meters – 110 meters, the depth of The Wenner configuration uses the geoelectrical resistivity method, with a leachate resistivity value of 0, 5 – 5 m is expected to identify the distribution of leachate in the measurement path. The results of the geoelectric test show that the leachate distribution in Track I is at a track length of 28 meters – 84 meters, a depth of 13 meters – 17.4 meters with a resistivity value of 2.18 m, Track II is at a track length of 7 meters. – 140 meters, a depth of 8.93 meters – 13.4 meters with a resistivity value of 2.95 m, and Track III at a length of 80 meters – 110 meters, a depth of 13 meters – 17.4 meters with a resistivity value of 0.807 m. This distribution is also influenced by drainage, soil elevation, soil type, and landfill management in sites city of Medan is the TPA Terjun.